Survivorship Care Plans in Cancer: A Meta‐Analysis and Systematic Review of Care Plan Outcomes. (25th October 2019) - Hill, Rebecca E.; Wakefield, Claire E.; Cohn, Richard J.; Fardell, Joanna E.; Brierley, Mary‐Ellen E.; Kothe, Emily; Jacobsen, Paul B.; Hetherington, Kate; Mercieca‐Bebber, Rebecca
Abstract: Background: The Institute of Medicine recommends that survivorship care plans (SCPs) be included in cancer survivorship care. Our meta‐analysis compares patient‐reported outcomes between SCP and no SCP (control) conditions for cancer survivors. Our systematic review examines the feasibility of implementing SCPs from survivors' and health care professionals' perspectives and the impact of SCPs on health care professionals' knowledge and survivorship care provision. Methods: We searched seven online databases (inception to April 22, 2018) for articles assessing SCP feasibility and health care professional outcomes. Randomized controlled trials comparing patient‐reported outcomes for SCP recipients versus controls were eligible for the meta‐analysis. We performed random‐effects meta‐analyses using pooled standardized mean differences for each patient‐reported outcome. Results: Eight articles were eligible for the meta‐analysis ( n = 1, 286 survivors) and 50 for the systematic review ( n = 18, 949 survivors; n = 3, 739 health care professionals). There were no significant differences between SCP recipients and controls at 6 months postintervention on self‐reported cancer and survivorship knowledge, physical functioning, satisfaction with information provision, or self‐efficacy or at 12 months on anxiety, cancer‐specific distress, depression, or satisfaction with follow‐up care. SCPs appear to be acceptable and potentially improve survivors' adherence to medical recommendations and health care professionals' knowledge of survivorship care and late effects. Conclusion: SCPs appear feasible but do not improve survivors' patient‐reported outcomes. Research should ascertain whether this is due to SCP ineffectiveness, implementation issues, or inappropriate research design of comparative effectiveness studies. Implications for Practice: Several organizations recommend that cancer survivors receive a survivorship care plan (SCP) after their cancer treatment; however, the impact of SCPs on cancer survivors and health care professionals is unclear. This systematic review suggests that although SCPs appear to be feasible and may improve health care professionals' knowledge of late effects and survivorship care, there is no evidence that SCPs affect cancer survivors' patient‐reported outcomes. In order to justify the ongoing implementation of SCPs, additional research should evaluate SCP implementation and the research design of comparative effectiveness studies. Discussion may also be needed regarding the possibility that SCPs are fundamentally ineffective. Abstract : This comprehensive systematic review evaluates the effect of survivorship care plans on cancer survivors and health care professionals.